2020
DOI: 10.5811/cpcem.2020.6.47856
|View full text |Cite
|
Sign up to set email alerts
|

Cardioembolic Stroke in a Patient with Coronavirus Disease of 2019 (COVID-19) Myocarditis: A Case Report

Abstract: Introduction: There is a growing body of literature detailing coronavirus 2019 (COVID-19) cardiovascular complications and hypercoagulability, although little has been published on venous or arterial thrombosis risk. Case Report: In this report, we present a single case of cardioembolic stroke in the setting of COVID-19 related myocarditis, diagnosed via cardiac magnetic resonance imaging and echocardiography. COVID-19 infection was confirmed via a ribonucleic acid polymerase chain reaction assay. Conclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Apart from coronary events that may lead to cardiac dysfunction, systematic inflammatory response or direct invasion of the SARS‐CoV‐2 may result in significant myocardial dysfunction. Several studies reported myocardial dysfunction in the setting of nonspecific myocarditis or Takotsubo cardiomyopathy in patients with COVID‐19 [71–73], which could be associated with ischemic stroke as reported recently [74,75]. Similarly, viral particles were reported in the interstitial macrophages of cardiac tissue of a patient with COVID‐19 and cardiogenic shock [72], whereas among COVID‐19 patients who underwent cardiac magnetic resonance imaging, 78% had cardiac involvement, and 60% had ongoing inflammation with lymphocytic infiltration [76].…”
Section: Methodsmentioning
confidence: 87%
“…Apart from coronary events that may lead to cardiac dysfunction, systematic inflammatory response or direct invasion of the SARS‐CoV‐2 may result in significant myocardial dysfunction. Several studies reported myocardial dysfunction in the setting of nonspecific myocarditis or Takotsubo cardiomyopathy in patients with COVID‐19 [71–73], which could be associated with ischemic stroke as reported recently [74,75]. Similarly, viral particles were reported in the interstitial macrophages of cardiac tissue of a patient with COVID‐19 and cardiogenic shock [72], whereas among COVID‐19 patients who underwent cardiac magnetic resonance imaging, 78% had cardiac involvement, and 60% had ongoing inflammation with lymphocytic infiltration [76].…”
Section: Methodsmentioning
confidence: 87%
“…5 Hypercoagulation during SARS-CoV-2 infection has been linked to cerebral embolism in several cases. 6,7 In our case, the patient was asymptomatic, and therefore, the duration of infection remains unknown. However, a second test performed 7 days after the positive one was already negative, thus suggesting that infection occurred earlier.…”
Section: Discussionmentioning
confidence: 78%
“… 5 Hypercoagulation during SARS-CoV-2 infection has been linked to cerebral embolism in several cases. (6) , (7) …”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a handful of cases resulting in ventricular thrombi caused by COVID-19 have been published. 1 , 2 , 3 , 4 , 5 , 6 , 7 All of the published cases were of relatively older patients (>40 years old). Additionally, another less common cardiovascular complication, with the most recent studies calculating an incidence of about 33%, 8 is COVID-related myocarditis.…”
Section: Introductionmentioning
confidence: 99%